The impact of port governance and infrastructures on maritime containerized trade on the West Coast of Latin America - Beatriz Lopez-Bermudez; Mariá Jesuś Freire-Seoane; Ignacio de la Pen\~a Zarzuelo (European Journal of Government and Economics (EJGE), 2018)
Latin American countries have historically had a strong dependence on trade, and are mostly characterized by being exporters of raw materials and importers of manufactured products. This fact has brought about a less negative impact of the world crisis on economic growth, mainly because of the high prices of raw materials.This paper focuses on this geographical area (the West Coast of Latin America) between 2008 and 2015, and adds to the literature by assessing institutional, port-related and economic factors that influence maritime transport. The analysis makes use of panel data models with fixed and random effects where the Hausman test has been applied in order to define a solid specification of all the ports, as well as to discount the particular peculiarities of each country.It is shown that the analysis of maritime transport requires the analysis of a number of variables apart from trade (volume of TEUs), infrastructures, superstructures (number of calls, gantry cranes), and that other variables, such as port governance, which are sometimes difficult to quantify, need also to be taken into account.
Keywords: 330; Port governance; maritime trade; Latin America; panel data